Procarboxypeptidase U (proCPU, TAFI, proCPB2) in cerebrospinal fluid during ischemic stroke is associated with stroke progression, outcome and blood–brain barrier dysfunction. (26th December 2017) - Mertens, J. C.; Leenaerts, D.; Brouns, R.; Engelborghs, S.; Ieven, M.; De Deyn, P. P.; Lambeir, A.‐M.; Hendriks, D.
Abstract : Essentials Little is known of procarboxypeptidase U (proCPU) in cerebrospinal fluid (CSF) of stroke patients. ProCPU levels were studied in CSF of controls and non‐thrombolyzed acute ischemic stroke patients. ProCPU is elevated in CSF of stroke patients compared with controls. ProCPU in CSF correlates with stroke progression, outcome, and blood‐brain barrier dysfunction. Summary: Background: Procarboxypeptidase U (proCPU, TAFI, proCPB2), the zymogen of CPU, which is a potent antifibrinolytic enzyme and a modulator of inflammation, has previously been investigated in plasma of stroke patients, but so far, no information on the proCPU levels in cerebrospinal fluid (CSF) during acute ischemic stroke (AIS) is available. Objectives: This case–control observational study investigates proCPU in CSF of AIS patients compared with controls with an intact blood–brain barrier (BBB) and evaluates the relationship of CSF/plasma proCPU ratios with stroke parameters. Methods: A sensitive HPLC‐based enzymatic assay was used to determine proCPU levels in CSF of non‐thrombolyzed patients in the hyperacute phase (< 24 h after onset) of AIS ( n = 72). Individuals ( n = 32) without stroke, an intact BBB and no apparent abnormalities in biochemical and microbiological tests, served as controls. Relations between the CSF/plasma proCPU ratio and (i) stroke severity, (ii) stroke progression/recurrence, (iii) stroke outcome and (iv) BBB dysfunction (CSF/serum albumin ratio) were assessed. Results: Mean (SEM) proCPU levels were elevated in the CSF of stroke patients compared with controls (4.36 (0.23) U L −1 vs. 3.50 (0.23) U L −1 ). Higher median [IQR] CSF/plasma proCPU ratios were found in patients with stroke progression ((6.0 [4.2–6.9]) × 10 −3 ) and poor outcome ((6.4 [3.9–7.0]) × 10 −3 ) after 3 months (modified Rankin Scale; mRS > 3) compared with patients without progression ((3.9 [2.7–5.4]) × 10 −3 ) or better outcome ((4.0 [2.8–5.0]) × 10 −3 ). In stroke patients with a disrupted BBB, proCPU ratios were higher compared with stroke patients with an intact BBB ((6.4 [5.8–9.0]) × 10 −3 vs. (3.7 [2.8–5.0]) × 10 −3 ). Conclusions: ProCPU is increased in CSF during hyperacute ischemic stroke and is associated with stroke progression and outcome after 3 months, most likely due to BBB dysfunction in the hyperacute phase of ischemic stroke.